Constraints hindering the development of communal livestock production and opportunities which exist in Nyandeni Local Municipality Eastern Cape Province South Africa - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2018)
Dissertation (MSc (Agric))--University of Pretoria, 2017.